A novel fast-qualitative balance test method of screening for vestibular disorder patients - Tran Anh Vu; Hoang Quang Huy; Le Van Tuan; Pham Thi Viet Huong (Institute of Advanced Engineering and Science, 2022)
Body balance test is one of the methods of assessing vestibular level. However, the results are still qualitative, depending on the subjectivity of the doctor. This study proposes a new, low-cost method to quantitatively determine the degree of body imbalance. The proposal includes a low-cost laser source, a proposed rectangular paper frame, a camera, and a computer. The rectangular frame is mounted on the patient. The laser source is fixed and projected onto this rectangular frame. The laser projection point is taken as the origin point to evaluate the movement of the frame, which is also the movement of the patient’s body. This rectangular frame is pre-marked with points to get more accuracy of the position of the laser point. Therefore, this measurement is not affected by the position of the camera during recording. The video is then procecced by computer to determine the position of laser point, it is also presented the movement of the patient’s body. Initial trials were conducted on vestibular and normal patients. The results show that there is a clear difference in the balance of the vestibular and healthy people. The proposed method can be used to support quantitative screening for vestibular disease.